Space production and its relation in the health process - family disease - Pareja, Juliana Maria Damelines; Guerra, Francismara Fernandes; Vieira, Sidnea Ribeiro; Teixeira, Karla Maria Damiano (Saúde e Sociedade, 2016)
This article aims to propose a social analysis of the process of health-illness in the family, developing the concept of space from the perspective of eco system theory and concept of social determinants of health. First, it is a discussion on the concept of "family", considering the social and ecological aspects of the order and reproduction principle. Then, a discussion on nutrition and work as forms of adaptation, strategies and administration of families' resources, to organize themselves in an ecosystem and as ecosystem, as to produce space. In this context, we tried to establish that the social production of space and its organization structure the living conditions of their ecosystems and forms of relationships between people and their environ ment, which can trigger the process health-disease.